Transação em conflitos transindividuais de consumo: análise no âmbito extrajudicial e judicial - Simão, Lucas Pinto (2017)
This work aims at the analysis of settlement in the context of consumer class actions in accordance to the Brazilian law. Therefore, initially, we will hold brief notes about difficulties on the access to justice within the context of a mass consumer society when there is a preeminent need to develop mechanisms to enable effective judicial protection of consumers. In this context, we will address the class action as an important instrument on the access to justice on a mass consumer society and will aim to delineate what is to be a class action and that defines the so called collective civil jurisdiction. In this step, it will be traced a brief overview of the class action in US law, English law, in some countries members of the European Union and in Brazil. At this time, a methodological cut will be made in the treatment of class actions as mechanisms on the access to justice, for the purpose of analyzing the settlement from the point of view of civil law and Brazilian civil law procedure. The settlement will be pointed out as an important form of consumer conflict resolution, we will check their requirements for the objective and subjective level, as well as its advantages and disadvantages. Next, we will study the settlement in the light of class actions in the Brazilian collective civil process, particularly those related to the protection of diffuse rights, collective and / or individual homogeneous rights of consumers. The concepts involved in a class action are much more complex than an ordinary individual process, which substantially changes the shape and even the possibility of being held a settlement on a conflict involving diffuse rights, collective and / or individual homogeneous rights of consumers. After tracing the difficulties of interpretation of the settlement in the Brazilian collective civil process, we will analyze the settlements in class actions according to US law and will be mention the advantages and / or disadvantages of using the US model of class action settlement in Brazilian law. In the final development, we will draw few lines on how to achieve the settlement involving collective conflict involving diffuse rights, collective and / or individual homogeneous rights of consumers, specifically analyzing alternative means of conflict resolution and the duty / power of the judge to encourage conciliation / mediation in consumer class actions. At the end, we will be able to establish a discussion of proposals that could allow better treatment for settlements involving consumer class actions